2019
DOI: 10.1016/j.jacc.2019.03.529
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Blood Pressure and Cholesterol Levels During Young Adulthood With Later Cardiovascular Events

Abstract: BACKGROUNDBlood pressure (BP) and cholesterol are major modifiable risk factors for cardiovascular disease (CVD), but effects of exposures during young adulthood on later life CVD risk have not been well quantified.OBJECTIVEThe authors sought to evaluate the independent associations between young adult exposures to risk factors and later life CVD risk, accounting for later life exposures.METHODSThe authors pooled data from 6 U.S. cohorts with observations spanning the life course from young adulthood to later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(137 citation statements)
references
References 48 publications
(59 reference statements)
2
130
0
5
Order By: Relevance
“…Therefore, we conducted sensitivity analyses across various scenarios to assess whether and to what extent the heterogeneity could be reduced. As a result, the heterogeneity reduced from substantial to moderate (supplementary appendix 3, table S2) when the analyses were confined to studies including only untreated participants81213192023 or when a mercury sphygmomanometer was used for blood pressure measurements 121314212223…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we conducted sensitivity analyses across various scenarios to assess whether and to what extent the heterogeneity could be reduced. As a result, the heterogeneity reduced from substantial to moderate (supplementary appendix 3, table S2) when the analyses were confined to studies including only untreated participants81213192023 or when a mercury sphygmomanometer was used for blood pressure measurements 121314212223…”
Section: Resultsmentioning
confidence: 99%
“…Six large community-based prospective cohorts identified that young adult exposures to major modifiable risk factors for cardiovascular disease (CVD) were associated with increased CVD risks in later life, independent of later adult exposures. 9 Except for the absolute level of BMI, longitudinal BMI trajectory across the lifecourse also plays an important role in the development of diabetes. [10][11][12][13][14] However, it is unclear whether the dynamic trends in body weight gain contribute to future diabetes risk, especially during young adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме этого, необходимо отметить, что, в соответствии с данными исследований последних лет, воздействие повышенного уровня ХС ЛПНП и АД даже в относительно молодом возрасте существенно увеличивает риск развития ССЗ [29][30][31]. Так, в исследовании Y. Zhang и соавт., объединившем данные о более чем 36 тыс пациентов из 6 крупных когортных исследований (ARIC, CARDIA, FHS-O, HealthABC, MESA, CHS), уровни ХС ЛПНП≥2,6 ммоль/л в возрасте 18-39 лет Is it Time for Anti-«Lipitensive» Therapy?…”
Section: теоретические предпосылки к одновременной коррекции повышеннunclassified
“…в этом же возрасте -с увеличением риска развития сердечной недостаточности на 37% (ОР 1,37; 95%ДИ 1,17-1,71) по сравнению с АД<120 мм рт.ст. [31]. Следует подчеркнуть, что полученные ассоциации не зависели от значений ХС ЛПНП и АД в более поздний период жизни, в связи с чем закономерно возникает вопрос о необходимости коррекции этих факторов риска в молодом возрасте.…”
Section: теоретические предпосылки к одновременной коррекции повышеннunclassified